BRD9 status is a major contributor for cysteine metabolic remodeling through MST and EAAT3 modulation in malignant melanoma - Hipólito, Ana (2024)
Publisher Copyright: Copyright © 2023 The Authors. Published by Elsevier B.V. All rights reserved.